Pembelajaran Kooperatif Tipe Think-Pair-Share dan Pembelajaran Berbasis Proyek dalam Meningkatkan Pemahaman Tata Bahasa Arab - Rohmat, Ali; Abidin, Zaenal (Ukazh: Journal of Arabic Studies, 2025)
Learning Arabic grammar often presents a significant challenge for students, necessitating innovative strategies to enhance comprehension. This research aims to analyze the comparative impact and simultaneous contribution of the Think-Pair-Share cooperative learning type and project-based learning on improving students' understanding of Arabic grammar. The research population comprised all students at STAI Syubbanul Wathon Magelang, with a random sample of 100 students selected. Research data were collected using questionnaires to measure the implementation of the learning methods and test results to evaluate Arabic grammar comprehension. Data analysis was conducted using multiple linear regression. The findings indicate that both methods, Think-Pair-Share and project-based learning, significantly contributed to the enhancement of students' Arabic grammar comprehension. Simultaneously, both methods had a positive and significant impact on grammar understanding. The implications of this study include recommendations to synergistically integrate these two learning strategies into the Arabic language curriculum and teaching practices to optimize learning outcomes. The novelty of this research lies in its simultaneous and comparative analysis of the impact of both methods on Arabic grammar comprehension within the context of Islamic higher education.